Pengaruh Aktivitas Rantai Nilai Terhadap Kualitas dan Inovasi Produk - Gerai Alun Segara; Titik Kusmantini; Yekti Utami (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
This study was inspired by the scarcity of furniture raw materials so that the furniture SMEs should regulate their value chain activities to maintain their product quality and innovation. The observed value chain dimensions in this study were customer focus, research and development management, process management and supplier management. This study was intended to find out the effect of value chain activities on product quality and innovation. The samples were 31 furniture SMEs in Bantul, Special Territory of Yogyakarta. They were selected through census. The data were then analyzed through multiple linear regression. The result showed that the customer focus affected both product quality and innovation, research and development management affected product innovation, process management affected product quality and supplier management influenced both product quality and innovation.